Two new species of the genus Anabropsis Rehn, 1901 (Orthoptera: Anostostomatidae) from Yunnan, China - Xu, Hao; Shi, Fuming (Zootaxa, 2024)
In this paper, two new species of the genus Anabropsis Rehn, 1901 from Yunnan, China, i.e. Anabropsis (Apteranabropsis) papiliomaculata sp. nov. and Anabropsis (Paterdecolyus) dulongjiangensis sp. nov. are described. In addition, the male of Anabropsis (Pseudapteranabropsis) nigrimaculatis Pang, Lu & Bian, 2023 is reported for the first time, and the species is transferred into Anabropsis (Apteranabropsis) Gorochov, 1988. All specimens are deposited in the Museum of Hebei University.